A Path Analysis of Effects of Patients' Underlying Conditions, Treatment Satisfaction, and Adherence on Quality of Life Among Korea Glaucoma Patients. Issue 9 (September 2019) - Kim, Chan Yun; Park, Ki Ho; Ahn, Jaehong; Ahn, Myung-Douk; Cha, Soon Cheol; Kim, Ho-Soong; Kim, Joon Mo; Kim, Moon Jung; Kim, Tae-Woo; Kim, Yong Yeon; Lee, Ji Woong; Park, Sang-Woo; et al.
Abstract : Précis: This observed patient-specific features and treatment-driven conditions that were significantly associated with the impairment of health-related quality of life (HRQOL) among glaucoma patients. The results suggest that more systematic strategies should be implemented to improve an HRQOL. Purpose: To determine factors contributing to an HRQOL and assess total, direct and indirect, effects that may exist between the determinants using path analysis. Materials and Methods: Data were derived from previous Korea glaucoma outcomes research. A total of 847 glaucoma outpatients with ⩽2 years of eye-drop use were included in the present study. Including factors and their hypothetical pathways to an HRQOL were based on the literature review and consultation with specialists. Age, sex, comorbidities, and education levels were included as underlying conditions and treatment patterns were defined by the number of daily instillations of prescribed eye-drops. Treatment satisfaction and adherence were estimated using a Treatment Satisfaction Questionnaire for Medication, which assessed side-effects, effectiveness, convenience, global satisfaction, and pill count. An HRQOL was assessed by EQ-5D and EQ-visual analogue scale (EQ-VAS). Results: In EQ-5D analysis, male individuals showed total effects (β=0.102, P =0.0026), including both direct (β=0.076, P =0.0095) and indirect effects (β=0.0253, P =0.0020), which were mediated by treatment satisfaction in the side effects and global satisfaction categories. Higher education (β=0.197, P =0.0020) and satisfaction in the side effect (β=0.095, P =0.0076) and global satisfaction (β=0.075, P =0.0414) categories were found to have direct effects on EQ-5D. For EQ-VAS, higher education levels had significant total effects (β=0.153, P =0.0020) accounting for direct effects (β=0.131, P =0.0030) and indirect effects (β=0.0223, P =0.0531) through global satisfaction. In addition, male individuals had indirect effects (β=0.274, P =0.0165), which was indirectly mediated by satisfaction in the global satisfaction category. Comorbidity (β=−0.096, P =0.0090) and satisfaction in the effectiveness (β=0.094, P =0.0302), convenience (β=0.076, P =0.0390), and global satisfaction (β =0.144, P =0.0020) categories showed indirect effect on EQ-VAS. Conclusion: Higher education and better treatment satisfaction had positive effects on HRQOL both in direct and indirect ways whereas comorbidities indirectly showed negative associations with HRQOL. Abstract : Supplemental Digital Content is available in the text.